2016
DOI: 10.1039/c6nr02448c
|View full text |Cite
|
Sign up to set email alerts
|

Glioma-targeted superparamagnetic iron oxide nanoparticles as drug-carrying vehicles for theranostic effects

Abstract: Multifunctional nanoparticles capable of the specific delivery of therapeutics to diseased cells and the real-time imaging of these sites have the potential to improve cancer treatment through personalized therapy. In this study, we have proposed a multifunctional nanoparticle that integrate magnetic targeting, drug-carrier functionality and real-time MRI imaging capabilities in one platform for the theranostic treatment of tumors. The multifunctional nanoparticle was designed with a superparamagnetic iron oxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
53
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(56 citation statements)
references
References 43 publications
3
53
0
Order By: Relevance
“…The study performed by Kouchesfehani, Kiani, Rostami, and Fakheri () demonstrated that IONP cytotoxicity was mainly dose‐dependent and a concentration of 10 μg/ml already reduced the proliferative activity of mouse embryonic stem cells. Conflicting data exist regarding the cytotoxicity of IONPs (Sonmez et al, ) , (Xu et al, ). It has been shown that not only the dose but also nanoparticle size and shape play an important role in cell toxicity (Lee et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The study performed by Kouchesfehani, Kiani, Rostami, and Fakheri () demonstrated that IONP cytotoxicity was mainly dose‐dependent and a concentration of 10 μg/ml already reduced the proliferative activity of mouse embryonic stem cells. Conflicting data exist regarding the cytotoxicity of IONPs (Sonmez et al, ) , (Xu et al, ). It has been shown that not only the dose but also nanoparticle size and shape play an important role in cell toxicity (Lee et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…A small activation volume is advantageous for treatments in which the target is well defined, e.g., a detectable solid tumor or blood clot. A broader activation volume could be preferable in concert with applications that require additional biological targeting to locate diseased regions …”
Section: Discussionmentioning
confidence: 99%
“…Chen et al [119] used copolymer of reducible polyamidoamine with polyethylene glycol/dodecyl amine for delivery of doxorubicin to targeted cells. Xu et al [120] prepared multifunctional nanoparticles by using a superparamagnetic iron oxide core with PEG/PEI/polysorbate 80 (Ps 80), and that was utilized to encapsulate DOX. As per the authors, the NPs were capable of delivering drugs effectively to gliomas.…”
Section: Polymeric Superparamagnetic Npsmentioning
confidence: 99%